Biochar from Agricultural Waste for Soil Amendment Candidate under Different Pyrolysis Temperatures - Abdul Mutolib; Ali Rahmat; Endra Triwisesa; H. Hidayat; Hari Hariadi; Kiki Kurniawan; S. Sutiharni; S. Sukamto (Universitas Pendidikan Indonesia, 2023)
Indonesia as an agricultural country produces and consumes a huge amount of fruits. One of the popular fruits is durian (Durio zibethinus), which can create issues with the high amount of durian seeds. Durian seeds can be fermented quickly. Thus, if they are not processed immediately, it causes pollution to the environment, particularly an odor issue. One of the waste management is to convert durian seed waste into biochar, an ameliorant agent to improve soil quality. This study aims to analyze the physicochemical properties of durian seed-derived biochar under different pyrolysis temperatures. The results showed that the increases in the temperature allowed the creation of more porosity in the biochars, which is due to chemical structure and crystallinity arrangement. This is confirmed by the increases in surface area and total pore volume also decreases in particle size. The change in the chemical structure can be verified by the decreases in the biochar yield. The produced biochar from fruit seeds has excellent carbon content and elemental components such as potassium, magnesium, phosphor, and sulfur, informing prospective fruit seeds as a soil amendment fertilizer